Cerasomes and Bicelles: Hybrid Bilayered Nanostructures With Silica-Like Surface in Cancer Theranostics - Hameed, Sadaf; Bhattarai, Pravin; Dai, Zhifei (Frontiers in Chemistry, 2018)
Over years, theranostic nanoplatforms have provided a new avenue for the diagnosis and treatment of various cancer types. To this end, a myriad of nanocarriers such as polymeric micelles, liposomes, and inorganic nanoparticles (NPs) with distinct physiochemical and biological properties are routinely investigated for preclinical and clinical studies. So far, liposomes have received great attention for various biomedical applications, however, it still suffers from insufficient morphological stability. On the other hand, inorganic NPs depicting excellent therapeutic ability have failed to address biocompatibility issues. This has raised a serious concern about the clinical approval of multifunctional organic or inorganic-based theranostic agents. Recently, partially silica coated nanohybrids such as cerasomes and bicelles demonstrating both diagnostic and therapeutic ability in a single system, have drawn profound attention as a fascinating novel drug delivery system. Compared with traditional liposomal or inorganic-based nanoformulations, this new and highly stable nanocarriers integrates the functional attributes of biomimetic liposomes and silica NPs, therefore, synergize strengths and functions, or even surpass weaknesses of individual components. This review at its best enlightens the emerging concept of such partially silica coated nanohybrids, fabrication strategies, and theranostic opportunities to combat cancer and related diseases.